ANALISIS KELAYAKAN INVESTASI JALAN TOL AKIBAT RESIKO KETERLAMBATAN PROYEK DAN KESALAHAN PREDIKSI LALU LINTAS (Studi Kasus: Jalan Tol Pejagan Pemalang) - Wahyudi, Riski; Nahdalina, Nahdalina (Jurnal Proyek Teknik Sipil, 2019)
Demand uncertainty and traffic forcase  uncertainty can lead to inaccuracies in the estimation of the revenues which are supposed to cover construction, operation and maintenance of toll roads. In addition, the delay in construction projects results an increase in the planned execution time of the project and increased in construction costs. This study focuses on the effect of project delays and the risk of traffic prediction in toll road project investments. The basis of this research is find out impact of the risks in project to feasibility analysis, so that the changes in the value of the investment feasibility indicator in bisnis plan can be obtained.  This study carried out using several technical economic methods to obtain the value of the investment feasibility indicator such as NPV, IRR, BCR and WACC. Pantura is the only one road which people use to move from Pejagan to Semarang. Therefore, an alternative road is needed to break traffic such as Pejagan-Pemalang Toll Road. Obtain from the calculation results, there are 4 risk comparison methods : analisis investmen according to business plan, project 2 years delay with business plan traffic, project on time with existing traffic after toll road operation and project 2 years delay with excisting traffic. The value of NPV, IRR and BCR after 2 years project delay with existing traffic  are Rp6,541,793,515,548,  9.1%, 1.239 and 8,5%. After comparison, the risk of construction delay affects significant changes in IRR and BCR, while the error traffic prediction results in a large NPV change, and the error in traffic assumption is the most influential risk for finance in the Pejagan Pemalang toll road construction project.